Effectiveness of an Educational Program Regarding Postpartum Care on Women’s Practices in Primary Health Care Centers at Amara City /Iraq - Rasha Leteef Neamah1 , Ezedeen F. Bahaaldeen2 , Iqbal Majeed Abbas3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: determined the effectiveness of educational program on women’s practices for Mothers’ Care in Postpartum Period in Primary Health Care Centers at Amara City. Methodology: Quasi-experimental design is accomplish on non-probability (Purposive sample) used to collect the data from 172 multigravida women, ( 86) study group and( 86) control group who were selected from the eight primary health care centers (AL-Uroba Primary Health Care Center, AL Zahraa Primary Health Care Center ,AL Hasen AL-Askerry Primary Health Care Center , AL-Qudis primary health care center, AL-Ameer primary health care center, AL-Jawideen primary health care center, AL- Amam AL Husaan. Primary health care center and Ali AL-Ridha Primary Health Care Center.) These centers are choose randomly from 16 primary health care centers in the first sector. The study was conducted from (1st December, 2018 to 1stDecember, 2019.). Results: The findings of the study indicated that (48%), (45%) respectively were in the age group (24-31) years for both study and control groups, a quarter of the both study and control group were primary school graduates, more than three quarter were housewives for both study and control groups , The majority of the women were living in urban area specifically for the study and control group, the majority of women in the study and control group were live equally of nuclear and extended families. Regarding to the reproductive characteristics more than a fifth women had five-six pregnancies for study group and quarter of the control group were had three pregnancies, and around a quarter of the study group were have three deliveries and more than fifth for control group were had two deliveries, as well as, three quarter of women in the both study and control group reported that they do not have abortion 64(74.4%), 62 (72.1%) respectively.